Financing Development: The Role of Information Costs - Greenwood, Jeremy; Sanchez, Juan M; Wang, Cheng (American Economic Review, 2010)
To address how technological progress in financial intermediation affects the economy, a costly-state verification framework is embedded into the standard growth model. The framework has two novel ingredients. First, firms differ in the risk/return combinations that they offer. Second, the efficacy of monitoring depends upon the amount of resources invested in the activity. A financial theory of firm size results. Undeserving firms are over-financed, deserving ones under-funded. Technological advance in intermediation leads to more capital accumulation and a redirection of funds away from unproductive firms toward productive ones. With continued progress, the economy approaches its first-best equilibrium. (JEL G21, G31, O16, O33, O41)